Reducing cognitive load in interfaces with a large number of workflows - Shumilina, Liudmyla (Global Prosperity, 2026)
Abstract. The article is devoted to the study of the problem of cognitive load in digital systems with a large number of workflows, in particular in SaaS platforms, cloud consoles and information dashboards. The purpose of the article is to identify the features of complex digital interfaces, analyze the cognitive difficulties that arise when working with them, and also substantiate approaches to reducing the cognitive load of users. To achieve the set goal, the following methods of scientific analysis were used in the study: analysis of scientific sources on the issues of usability and human interaction with information systems; comparative analysis of approaches to optimizing interfaces of complex digital platforms; generalization of research results on factors of cognitive overload in systems with high data density and workflows. The results of the study showed that the interfaces of systems with a large number of workflows are characterized by a number of structural difficulties. These include the difficulty of navigating between functional sections of the system, the multi-step nature of operational procedures, the overload of the interface with information elements, and the difficulty of adapting to new users. It has been established that the main cognitive difficulties when interacting with such systems are the overload of the user's short-term memory, the difficulty of orientation in the interface structure, the excessive number of information indicators, frequent context switching between tools, and the increased probability of errors when configuring system parameters. The generalization of modern research has allowed us to systematize approaches to reducing cognitive load, among which optimization of the interface structure, improvement of information dashboards, consolidation of digital tools, and standardization of monitoring of complex IT systems are highlighted. The practical significance of the study lies in the application of the author's Systems-to-Interfaces (S2I) methodology, which involves the transformation of the system logic of a software product into understandable interface work scenarios focused on real operational processes and user roles.